E-uprava deset milisekund po velikem poku - Vintar, Mirko (Uporabna informatika (Ljubljana), 2001)
Although much has been written about e-government, it has been considered primarily as a technological problem. It is becoming evident, though, that thedevelopment of e-government requires profound changes in basic organisational principles and particularly in business processes, too. The article considers management and organisational points of view of e-government phenomenom. E-government radically changes internal organisational and process structure of government systems and the technological basis of their operations. Moreover, it changes the ways of communication with its users, citizens and organisations, the nature and quality of its services. We shall define hte nature of that change and basic principles which should be taken into account at further development of e-government.
Keywords: elektronsko poslovanje; informacijski sistemi; javna uprava; razvoj